220 MANAGING CARDIAC ARREST SECONDARY TO SPONTANEOUS CORONARY ARTERY DISSECTION: SHOULD WE ROUTINELY CONSIDER ICD IMPLANTATION?. (15th December 2022) - Rizzello, Davide; Gurgoglione, Filippo Luca; Giacalone, Rossella; Ferretti, Marco; Noni, Manjola; Pelà, Giovanna; Cattabiani, Maria Alberta; Benatti, Giorgio; Tadonio, Iacopo; Ardissino, Diego; Niccoli, Giampaolo; Vignali, Luigi; et al.
Abstract: Introduction: Cardiac arrest secondary to a spontaneous coronary artery dissection (SCAD) represents a challenging scenario. It deserves specific considerations due to the dramatic presentation and the need for secondary sudden cardiac death prevention. Methods: We collected clinical data of four women admitted during the last two years in the Coronary Care Unit of Parma University Hospital, whose presentation of SCAD were cardiac arrest due to ventricular fibrillation. Results: Three patients survived the acute phases. One patient, being considered at high risk of SCAD recurrence, received a subcutaneous implantable cardioverter-defibrillator (S-ICD). A cute management of cardiac arrest related to SCAD deserves specific considerations. Our case series illustrates the importance of prompt resuscitation manoeuvres and early defibrillation. We propose a flow chart of management of cardiac arrest in patient with suspect of SCAD. Evaluating risk of SCAD recurrence and sudden cardiac death The management of SCAD patients complicated by malignant ventricular arrhythmias and cardiac arrest is challenging. Looking at published registries, it appears that SCAD patients are more likely to suffer from ventricular arrythmia or sudden cardiac death than non-SCAD MI patients. The risk-benefit ratio of ICD implantation in these patients remain uncertain . Evaluation of scar burden with CMR can help stratify the global arrhythmic risk, especially as extensive myocardial scar with a residual impaired LVEF increases the risk of future arrhythmic events. In our series, only one patient underwent S-ICD implantation, and the decision was mainly driven by the finding of underlying arteriopathy affecting other vascular territories, suggesting a potentially higher rate of SCAD recurrence. For this particular subset of patients, we propose an algorithm that combines predisposing factors and myocardia injury quantification data that could be useful for the estimate of the risk of malignant arrythmias, as well as the risk of recurrence of SCAD, but needs to be validated in larger case studies. Conclusions: The acute management of cardiac arrest related to SCAD deserves specific consideration. The residual myocardial damage, predisposing and precipitants factors should be evaluated in order to estimate the SCAD recurrence and sudden cardiac death risks.